Books of Accounts for the Purpose of Both Financial and Tax Reporting in Light of the Changes Taking Place at the Turn of the 21st Century - Kluzek , Marta (Studia Oeconomica Posnaniensia, 2014)
Books of accounts serve multiple tasks, but in a developed market environment their primary function is information. This article presents the information needs of a particular user of financial accounting - the tax administration. The purpose of this article is to present the reasons for the differences between tax law and the balance sheet, particularly in relation to the category of financial results, and the consequences of this state of affairs for businesses. A tax legislator adjusts the gross income for the purposes of taxation, or ignores this category completely, defining corporate taxable income according to different rules. The separation between accounting law and tax law stems from different principles underlying these two legal branches. The accounting systems of individual countries increasingly follow the Anglo-Saxon model, which satisfies primarily the information needs of investors, whereas tax law systems remain national systems. The current form of the Accounting Act now in force in Poland, as a result harmonization and standardization processes, is an attempt to combine the continental and Anglo-Saxon models. The diversity in the principles underlying accounting law and tax law does not mean that finding a common approach is not possible. However, considering the changes taking place in both areas, determined by developments occurring around the world, this goal seems difficult to achieve, and making separate balance-sheet and tax calculations in companies is becoming more and more time-consuming.